(untitled) (Research, Society and Development, 2022)
Yogurt is one of the most popular fermented dairy products and an excellent vehicle for delivering functional ingredients such as prebiotics. In yogurts, prebiotics can act as a substrate for the growth of the intestinal microbiota, improving gastrointestinal functions and the immune system. Given this context, the present work aimed to evaluate the influence of the addition of three prebiotics such as lactulose, resistant dextrin and fructo-oligosaccharides up to a concentration of 5 %, on the physicochemical, texturometric and sensorial characteristics of Greek yogurt through a Simplex-Lattice Mix Planning. The dependent variables studied were: dry extract, total titratable acidity, pH, firmness and acceptance. Through the Response Surface methodology, it was observed that the independent variables showed statistically significant effects (p<0.10) for dry extract, texture and acceptance. The independent variables did not influence acidity and pH. The dry extract and the firmness of the yogurts were lower when using a higher concentration of lactulose. In contrast, yogurts with the highest concentration of lactulose received the highest acceptance scores. The optimized formulation was obtained with 5 % lactulose, 0 % resistant dextrin and 0 % fructo-oligosaccharides with a success probability of 98.21 %. Considering the optimal point, a serving of 120 g of Greek yogurt will contain the amount of lactulose recommended by Anvisa, which is 3.0 g per serving.